2021
DOI: 10.21203/rs.3.rs-243472/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brain 18F-FDG PET for the diagnosis of autoimmune encephalitis: a systematic review and a meta-analysis

Abstract: Objective: To consolidate current understanding of detection sensitivity of brain 18F-FDG PET scans in the diagnosis of autoimmune encephalitis and to define specific metabolic imaging patterns for the most frequently occurring autoantibodies. Methods: A systematic and exhaustive search of data available in the literature was performed by querying the PubMed/MEDLINE and Cochrane databases for the search terms: "FDG PET" and “"encephalitis" or "brain inflammation"”. Studies had to satisfy the following criteria… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…A further novelty of our case is detailed information about 18 F -FDG PET and FET PET within double positive anti-NMDAR and anti-MOG patients. Published data are subsumed in the Supplemental Table . Previous studies have already reported that in NMDAR encephalitis 18 F -FDG PET can reveal both hypo-and hypermetabolism [42]. With our case, we contribute longitudinal data of four 18 F -FDG PET scans and one FET PET scan.…”
Section: Discussionmentioning
confidence: 86%
“…A further novelty of our case is detailed information about 18 F -FDG PET and FET PET within double positive anti-NMDAR and anti-MOG patients. Published data are subsumed in the Supplemental Table . Previous studies have already reported that in NMDAR encephalitis 18 F -FDG PET can reveal both hypo-and hypermetabolism [42]. With our case, we contribute longitudinal data of four 18 F -FDG PET scans and one FET PET scan.…”
Section: Discussionmentioning
confidence: 86%
“…Firstly, FDG‐PET changes reflected functional abnormality developing earlier than the structural changes on MRI, which contributed a lot to early diagnosis and subsequent treatment. Secondly, some autoimmune encephalitis revealed specific metabolic changes because of the distinction of antigen distribution 2,46 . Thirdly, different antibodies may cause metabolic abnormalities in the same regions of brain, with the manifestations of corresponding anatomical syndromes, such as limbic encephalitis, striatal encephalitis, brainstem encephalitis, and cerebellar degeneration 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, some autoimmune encephalitis revealed specific metabolic changes because of the distinction of antigen distribution. 2,46 Thirdly, different antibodies may cause metabolic abnormalities in the same regions of brain, with the manifestations of corresponding anatomical syndromes, such as limbic encephalitis, striatal encephalitis, brainstem encephalitis, and cerebellar degeneration. 47 Fourthly, FDG-PET tend to show hypermetabolism in acute phase but hypometabolism or normal FDG uptake in chronic phase, which help us to understand the evolution of AE and detect the pathophysiological mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…(1) The crosssectional and retrospective nature of current study could not determine other potential risk factors associated with NSAbs in the elderly with new-onset and symptomatic seizures or epilepsy of unknown etiology, such as 18 F-fluorodeoxy-glucose positron emission tomography ( 18 F-FDG-PET). Prior studies have shown that 18 F-FDG-PET may play a key role in the diagnosis of autoimmune encephalitis, 35 but these imaging data were not available for all included patients in this retrospective study. Additionally, we did not cover the entire repertoire testing for NSAbs, such as novel DPPX, IgLON5, which may lead to underestimation of positive NSAbs and our nomogram may be corrected in the future with recognition of novel NSAbs.…”
Section: Discussionmentioning
confidence: 99%